Pašvaldību brīvprātīgas iniciatīvas - Vucāns, Rūdolfs (Latvijas Universitāte, 2023)
Bakalaura darbā pētīts līdz šim Latvijas Republikas tiesību zinātnē maz aplūkots jautājums par pašvaldību brīvprātīgo iniciatīvu izpratni. Novērojot brīvprātīgo iniciatīvu dažādo interpretāciju tiesību sistēmā, rodas sarežģīti jautājumi par brīvprātīgo iniciatīvu pielietošanu praksē un to nošķiršanu no pašvaldību autonomajām funkcijām. Pētījumam ir zinātniska un praktiska nozīme jēdzienu interpretācijas noskaidrošanai un pielietošanai nākotnē. Darba ietvaros atklāts brīvprātīgo iniciatīvu jēdziens, kā arī šī juridiskā instrumenta pielietošanas un regulēšanas problēmjautājumi, sniedzot potenciālus risinājumus.

The Bachelor’s thesis focuses on a scarcely looked at issue regarding the understanding of local governments’ voluntary initiatives within the Republic of Latvia. Observing the varying interpretations of voluntary initiatives in the system of law, complicated questions are raised about the voluntary initiative use in practice and their separation from local governents’ autonomous functions. The research has a scientific and practical use for understanding the correct interpretation of the aforementioned definitions and their correct use in future practice. In the confounds of this thesis, the voluntary initiative definition, as well as the problems of their use and enforcement are made overt, while providing potential solutions.
Local government free initiative
Keywords: Juridiskā zinātne; pašvaldības; brīvprātīgā inciatīva; autonomā funkcija; saistošie noteikumi; pašvaldību kontrole